Beuet Seumubeuet of Dayah Ulama as A Communication Model in Islamic Political Transformation in Aceh - Ahyar; Abdullah; Annai Saburi (Mediakita, 2026)
This study examines the transformation of Beuet Seumubeuet from a religious teaching tradition into a political communication model used by Dayah Ulama in the dynamics of Islamic political change in Aceh, particularly in the emergence and consolidation of the PAS-Aceh Local Party. The tradition, which initially served as a medium for transmitting religious values based on local wisdom, has now developed into a strategic instrument for shaping public opinion and strengthening the legitimacy of religion-based politics. The purpose of this study is to analyze the political communication practices of Dayah Ulama, trace the development of political discourse articulated in Beuet Seumubeuet, and explain the role of this tradition in the process of transformation of local Islamic politics. Using a qualitative approach with a phenomenological method, data were collected through in-depth interviews and participant observation with document and social media content analysis. Data were analyzed based on the stages of bracketing, reduction, imaginative variation, and synthesis of meaning. The results show that Beuet Seumubeuet is no longer merely a traditional religious practice. It has served as a dynamic and adaptive communication model. Through this tradition, Dayah Ulama can translate theological principles into effective political messages, build public trust, and shape policy orientations aligned with Islamic values. These findings confirm the assertion that Beuet Seumubeuet is a structured mechanism that has played a significant role in transforming Islamic politics in Aceh. Thus, this study contributes conceptually and empirically to the understanding of the relationship between religious authority, political communication, and socio-political change in Aceh.